Peripheral immune and metabolic regulation of Aβ and Tau by exercise in Alzheimer’s disease - Yu, Yuehan; Chen, Kang (Frontiers in Immunology, 2025)
Alzheimer’s disease (AD), characterized by the pathological accumulation of amyloid-β (Aβ) and hyperphosphorylated Tau proteins, remains a major global health challenge with limited therapeutic options. Recent findings highlight that peripheral immune and metabolic pathways play a pivotal role in regulating brain Aβ and Tau homeostasis, particularly in response to physical exercise. In this review, we comprehensively examine current clinical and preclinical evidence on how exercise modulates peripheral immune responses, metabolic states, and systemic clearance mechanisms—including hepatic, renal, immune, and glymphatic pathways. We discuss how regular exercise suppresses peripheral inflammation, enhances immune cell–mediated phagocytosis, improves metabolic resilience, and promotes the elimination of neurotoxic proteins. Furthermore, exercise-induced peripheral mediators, such as myokines, non-coding RNAs, and lactate, are shown to mediate inter-organ communication and signaling pathway crosstalk and contribute to neuroprotection. This integrative perspective underscores the therapeutic promise of exercise as a non-pharmacological intervention that targets peripheral immune-metabolic networks to mitigate AD pathology.